THE USAGE OF EUPHEMISMS IN COMMUNICATION - Mardanova Mokhira Davron kizi (Journal of new century innovations, 2022)
Abstract: The given article deals with the study about origins of English and Uzbek euphemisms in spoken language .We try to define some similarities and differences of euphemisms both languages with examples and definitions, which is being used over the countries.